An alpine enigma: Plant pathogens at Kosciuszko, Australia—A review - Paul L. Guy; Adrian J. Gibbs (Arctic, Antarctic, and Alpine Research)
Two plant viruses and a microcyclic rust infect a rare endemic species (Cardamine robusta Brassicaceae) near the highest point in Australia in the Kosciuszko alpine zone. Cardamine chlorotic fleck virus is only recorded from this species and turnip yellow mosaic virus’s only recorded Southern Hemisphere host is C. robusta even though it is surrounded by susceptible native and introduced species. Eurasia is hypothesized as the area of origin for Cardamine spp. The genus rapidly colonized and diversified in the Northern Hemisphere. Later it spread across vast distances to the Southern Hemisphere as several distinct lineages. The rust Puccinia cruciferarum infects C. robusta at Kosciuszko and Cardamine spp. in New Zealand and South America. The rust’s distribution and genetic diversity provide one possible route for the pathogens’ arrival in Southeast Australia. This review is the first synthesis of studies on these pathogens in the Australian alps and highlights the enigma they present.